Military Power : Explaining Victory and Defeat in Modern Battle - Biddle, Stephen (New Delhi, India Manas Publications, 2005)
Among the most important books ever published on modern warfare. The author fundamentally rethinks the causes of victory and defeat in modern war and challenges almost the entire corpus of scholarship on assessing force capability and the role of offense and defense in determining war outcomes.
Include Tables, Map, Garphs, Notes, Appendix and Index
Keywords: Military art and science -- Military history, Modern -- Offensive (Military science) -- Defensive (Military science)